Composite sandwich structures for crashworthiness applications - Tarlochan F.; Hamouda A.M.S.; Mahdi E.; Sahari B.B. (2023)
Fibre-reinforced polymer sandwiches are promising materials for reducing vehicle mass, thereby improving the fuel economics. Nonetheless, to fully explore these materials as the primary structures and energy absorbers in vehicles, it is important to understand the energy absorption capabilities of these materials. Hence, in the present work, comprehensive experimental investigation on the response of composite sandwich panels to quasi-static compression has been carried out. The crashworthiness parameters, namely the peak load, absorbed crash energy, specific absorbed energy, average crushing load, stroke efficiency, and crush force efficiency of various types of composite sandwich panels were investigated in a series of edgewise compression tests. The composite sandwich panels tested consists of several designs, such as C-shaped, wrapped, and with composite inserts in the core of the panel. The tested composite sandwich specimens were primarily fabricated from glass fibre. For some of the designs, Kevlar and carbon fibres were used. For the core material, two different types of polymeric foams, polystyrene and Polyurethane, were used with densities close to 30 kg/m3. Several modes of failure were observed and recorded. The primary mode of failure observed was progressive crushing with capabilities of high energy absorption and high stroke efficiencies. Particular attention is paid on the analysis of the mechanism of progressive crushing of the sandwich panels and its relation to the energy absorption capabilities. This is a vital information for designing these materials as energy absorbers. IMechE 2007.